Diversification of Farming Systems in Poland in the Years 2006-2009 - Kołodziejczak, Anna; Kossowski, Tomasz (Quaestiones Geographicae, 2011)
The use of methods based on the Gini coefficient and the Lorenz curve in studies of the spatial structure of agriculture offers a great possibility of presenting changes in it and assessing their causes. They provided a basis for a research on changes in the farming systems employed in Polish agriculture over the years 2006-2009. The results confirm there to be a further diversification of this sector of the economy, and even if slower than in the previous years, it shows agriculture to keep adapting to natural and economic conditions.